Hubungan Antara Minat Terhadap Komik Jepang (Manga) Dengan Kemampuan Rekognisi Emosi Melalui Ekspresi Wajah - Nian Astiningrum; Johana Endang Prawitasari (Jurnal Psikologi, 2007)
This study was conducted to find out if there’s a positive correlation between one’s interest to Japanese Comics (Manga) and his/her ability to recognize emotion through facial expression. The subject of this study (N=80) are high school students in SMA N 2 Yogyakarta, whose age ranged from 16 to 18 years old or in first and second grade. A questionnaire to measure interest to Japanese Comics (Manga) and a test consist of 55 pictures of facial expression of emotion taken from 25 comic books in seven Japanese Comics stories to measure ability to recognize emotion from facial expression are conducted. The correlation technique of Product Moment by Pearson is use for data analyzing. The result indicate the positive and significant relationship between one’s interest to Japanese Comics (Manga) and his/her ability to recognize emotion through facial expression (r=0,358; p=0,002